Poliomyelitis: choosing the right vaccine for safer protection - Narimak Awin,; Raman Ismail, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2005)
Program towards eradication of Poliomyelitis in developing countries is moving rapidly. Eradication of wild poliovirus jPom the Western Pacific region was achieved in October 2000. The key to poliomyelitis eradication in the world lies in the Indian subcontinent, and if success is achieved there, eradication elsewhere becomes a matter of time. However, the use of OPV is frequently followed by sporadic or even epidemic vaccine - associated polio. There are 2 excellent polio vaccines available. OPV has served us well, but the time has come to ask whether the risk of imported disease is greater or lesser then the sporadic and occasionally epidemic OPV associated poliomyelitis. The tradeoff seems to be between the safety ofIPV and the secondary gain in immunization afforded by the spread of OP V strains to contacts. Public Health circumstances are not static when wild poliovirus strains were circulating abundantly, if made good sense to abort that circulation rapidly by the application of OPV. The cases of VAPP could be seen as the price that had to be paid in order to keep polio at bay. Now, in 2003, we face a different set of circumstances. Wild poliovirus no longer exist in the Western Pacific region and polio incidence is falling elsewhere. Therefore the substitution of IPV for OPV as has happened in North America and Europe, deserves new consideration for countries in this region including Malaysia.